Are soluble ST2 levels influenced by vitamin D and/or the seasons?. Issue 6 (June 2019) - Francic, Vito; Keppel, Martin; Schwetz, Verena; Trummer, Christian; Pandis, Marlene; Borzan, Valentin; Grübler, Martin R; Verheyen, Nicolas D; Kleber, Marcus E; Delgado, Graciela; Moissl, Angela P; Dieplinger, Benjamin; et al.
Abstract : Objective: Cardiovascular disease manifestation and several associated surrogate markers, such as vitamin D, have shown substantial seasonal variation. A promising cardiovascular biomarker, soluble ST2 (sST2), has not been investigated in this regard – we therefore determined if systemic levels of sST2 are affected by seasonality and/or vitamin D in order to investigate their clinical interrelation and usability. Design: sST2 levels were measured in two cohorts involving hypertensive patients at cardiovascular risk, the Styrian Vitamin D Hypertension Trial (study A; RCT design, 8 weeks 2800 IU cholecalciferol daily) and the Ludwigshafen Risk and Cardiovascular Health Study (LURIC; study B; cross-sectional design). Methods: The effects of a vitamin D intervention on sST2 levels were determined in study A using ANCOVA, while seasonality of sST2 levels was determined in study B using ANOVA. Results: The concentrations of sST2 remained unchanged by a vitamin D intervention in study A, with a mean treatment effect (95% confidence interval) of 0.1 (−0.6 to 0.8) ng/mL; P = 0.761), despite a rise in 25(OH)D (11.3 (9.2–13.5) ng/mL; P < 0.001) compared to placebo. In study B, seasonal variations were present in 25(OH)D levels in men and women with or without heart failure ( P < 0.001 for all subgroups), while sST2 levels remained unaffected by the seasons in all subgroups. Conclusions: Our study provides the first evidence that systemic sST2 levels are not interrelated with vitamin D levels or influenced by the seasons in subjects at cardiovascular risk.